Poioumenon and Performative Storytelling in Canadian Fiction - Fisher, Sheldon (Studies in Canadian Literature, 1997)
No Canadian writer has been as insistent in the belief that life and story -- that living the story and storying the life -- are two sides of the same experience as has Robert Kroetsch. In his para-autobiography, A Likely Story: The Writing Life, Kroetsch spends much time talking around this very idea, dealing extensively with issues of performative self-/historical construction. In fact, it is extremely fruitful to examine a particular strand in Canadian fiction, what Alistair Fowler calls poioumenon (that is, novels in which the main plot is itself about the writing of a novel), using Kroetsch's theory as a lens. Such analysis can be extended both backwards and forwards to provide illuminating readings of texts as varied as Laurence's The Diviners, Callaghan's A Fine and Private Place, Davies's Deptford Trilogy, and Vassanji's The Book of Secrets. Each of these works, along with numerous others, neatly fits Kroetsch's theory that by telling, we create.